Soteriologi Buddhis: Jalan Arhat dan Jalan Boddhisattva - Novian Widiadharma; Lasiyo Lasiyo; Sindung Tjahjadi (UIN Sunan Kalijaga Yogyakarta, 2023)
Soteriology is a branch of theology that studies salvation which provides a framework for understanding how individuals can achieve spiritual liberation and offers guidance on how to live a good life. The specific beliefs and practices associated with them may vary between different religions, but the concept of salvation is a common thread that exists across many religions. Soteriology is important in Buddhism because it provides a framework for attaining liberation from suffering and the cycle of rebirth. The ultimate goal of Buddhism is to attain Nirvāna, the state of complete liberation from suffering. The Catvāri Āryasatyānī (Four Noble Truths), Āryāṣṭānga mārga (Noble Eightfold Path), and other Buddhist teachings all contribute to the Buddhist soteriological framework. Hinayāna and Mahāyāna are two main branches of Buddhism that have different approaches to soteriology. The goal of Hinayāna soteriology is to attain the state of an Arhat, a state of complete personal liberation from suffering and rebirth. While Mahāyāna has the Bodhisattva concept. The ultimate aim of Mahāyāna soteriology is to attain Buddhahood, the state of perfect enlightenment, and use that attainment for the benefit of all sentient beings. They provide guidance for practitioners to develop ethical conduct, wisdom, and mindfulness to advance on the path to liberation.